INTEGRATING LUWU CULTURE INTO ENGLISH LEARNING: A DEVELOPMENT OF CUSTOMIZED MATERIALS FOR NURSING STUDENTS - Lestari, Junita Anjar; Rustan, Edhy; Thayyib, Magfirah (University of Kuningan, 2024)
This research aimed to fulfill the need of nursing students to master English with the integration of local culture. This research was conducted at Kurnia Jaya Persada Health and Business Institute, Palopo City, South Sulawesi, Indonesia, from March to May 2023. This study was a research and development through four stages: (1) needs analysis, (2) material design, (3) try-out, and (4) material revision. The need analysis was done by administering the questionnaire to 32 nursing students and interviewing four English lecturers in the study program. The English material developed consists of seven units. The tasks in each unit integrate the language aspects and skills. The materials for nursing provided are vocabulary and expressions in the health field also English skills for nursing. The features of Luwu local culture in the material are the local names in the tasks; the pictures of the traditional letters, costumes, houses, and sites; the reading text about the culture and history of Luwu; the specialized unit entitled ‘My Local Culture’; the sub-topic about cross-culture communication; and the video about Luwu culture. The English material was judged by the four English lecturers with a mean score of 96.3. The material is valid with revision. The total response of the students toward the English material, after having the try-out stage, is 95.8% agree. The students have positive responses toward the English material.